How the whale got his throat - Kelly, Miles; Ranucci, Claudia (United Kingdom : Miles Kelly Publishing, 2016)
Rudyard Kipling's brilliantly funny tale of How the Whale got his Throat has been perfectly captured by Claudia Ranucci's bright, beautiful illustrations. Every page showcases delightful full-bled artwork, packed with charm and detail that will enthrall young children. The story has been simply retold to appeal to young readers and listeners alike.
Primary
800-899
Keywords: Children's stories; Whales -- Juvenile fiction